Combined Effect of Carbonation and Chloride Aggression: Reliability and Safety of Reinforced Concrete Structures - E. E., Shalyi; S. N., Leonovich; L. V, Kim (European Journal of Life Safety and Stability (2660-9630), 2022)
Corrosion reinforcement marine hydraulic structures due to chloride aggression and carbonization of concrete leads to a sharp decrease in the safety of the structure. The steel reinforcement will be subjected to a so-called depassivation process, once the chloride concentration on surface exceeds a certain threshold concentration, or the pH value in the protective layer of concrete decreases to a threshold value due to carbonation. Electrochemical reactions begin to occur with the formation of corrosion products with the penetration of oxygen on the steel reinforcement surface. This leads to cracking of the protective layer of concrete. It should also be taken into account that, due to corrosion mechanisms, the cross-sectional area of the reinforcement also decreases. The article suggests a method for predicting the complex degradation of reinforced concrete structures, taking into account various mechanisms of corrosion wear, which will allow developing effective ways to improve the durability and maintainability of structures operated in the marine environment